CSF chitinase 3-like 1 is associated with iron rims in patients with a first demyelinating event. (January 2022) - Comabella, Manuel; Clarke, Margareta A; Schaedelin, Sabine; Tintoré, Mar; Pareto, Deborah; Fissolo, Nicolás; Pinteac, Rucsanda; Granziera, Cristina; Sastre-Garriga, Jaume; Benkert, Pascal; Auger, Cristina; Kuhle, Jens; et al.
Background: Chronic active lesions with iron rims have prognostic implications in patients with multiple sclerosis. Objective: To assess the relationship between iron rims and levels of chitinase 3-like 1 (CHI3L1), neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAP) in patients with a first demyelinating event. Methods: Iron rims were identified using 3T susceptibility-weighted imaging. Serum NfL and GFAP levels were measured by single-molecule array assays. CSF (cerebrospinal fluid) CHI3L1 levels were measured by enzyme-linked immunosorbent assay (ELISA). Results: Sixty-one patients were included in the study. The presence of iron rims was associated with higher T2 lesion volume and higher number of gadolinium-enhancing lesions. In univariable analysis, having ⩾2 iron rims (vs 0) was associated with increased CSF CHI3L1 levels (β = 1.41; 95% confidence interval (CI) = 1.10–1.79; p < 0.01) and serum NfL levels (β = 2.30; 95% CI = 1.47–3.60; p < 0.01). In multivariable analysis, however, only CSF CHI3L1 levels remained significantly associated with the presence of iron rim lesions (β = 1.45; 95% CI = 1.11–1.90; p < 0.01). The presence of ⩾2 iron rims was not associated with increased serum GFAP levels in univariable or multivariable analyses. Conclusion: These findings support an important contribution of activated microglia/macrophages to the pathophysiology of chronic active lesions with iron rims in patients with a first demyelinating event.